2020
DOI: 10.1371/journal.pone.0230820
|View full text |Cite
|
Sign up to set email alerts
|

Combined QTL mapping and RNA-Seq profiling reveals candidate genes associated with cadmium tolerance in barley

Abstract: The high toxicity of cadmium (Cd) and its ready uptake by plants has become a major agricultural problem. To investigate the genetic architecture and genetic regulation of Cd tolerance in barley, we conducted quantitative trait loci (QTL) analysis in the phenotypically polymorphic Oregon Wolfe Barley (OWB) mapping population, derived from a cross between Rec and Dom parental genotypes. Through evaluating the Cd tolerance of 87 available doubled haploid lines of the OWB mapping population at the seedling stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…The role of selected ZIP transporters has been studied extensively in monocots (Li et al, 2013;Evens et al, 2017;Zheng et al, 2018) including barley (Pedas et al, 2009;Tiong et al, 2015). Interestingly, QTL mapping in barley identified two ZIP transcripts among the candidate genes for Cd tolerance (Derakhshani et al, 2020). In our dataset, we identified three previously studied ZIP transporters-HvZIP1 (HORVU.MOREX.r2.3HG0273580), HvZIP3 (HORVU.MOREX.r2.2HG0158440), and HvZIP6 (HORVU.MOREX.r2.1HG0020460).…”
Section: Metal Transportmentioning
confidence: 93%
See 1 more Smart Citation
“…The role of selected ZIP transporters has been studied extensively in monocots (Li et al, 2013;Evens et al, 2017;Zheng et al, 2018) including barley (Pedas et al, 2009;Tiong et al, 2015). Interestingly, QTL mapping in barley identified two ZIP transcripts among the candidate genes for Cd tolerance (Derakhshani et al, 2020). In our dataset, we identified three previously studied ZIP transporters-HvZIP1 (HORVU.MOREX.r2.3HG0273580), HvZIP3 (HORVU.MOREX.r2.2HG0158440), and HvZIP6 (HORVU.MOREX.r2.1HG0020460).…”
Section: Metal Transportmentioning
confidence: 93%
“…The total number of DE transcripts were lower in shoots (7,104) than in roots (10,282), consistent with the Cd concentration level detected in both tissues (Figures 1C,D). Previous transcriptomic studies reporting the effect of cadmium on barley focused on Cd tolerance, rather than response to Cd excess (Cao et al, 2014;Derakhshani et al, 2020). As the general objective of our study was to describe the overall response to cadmium in barley, we identified higher number of differentially expressed transcripts.…”
Section: Differentially Expressed Transcriptsmentioning
confidence: 96%
“…For example, the genetic architecture and regulation of Cd tolerance in barley plants identified two QTLs, one minor-effect and other major-effect QTL, with a phenotypic variance of 47.24 and 38.59%, respectively, associated with Cd tolerance. This analysis also identified 16 candidate genes linked with Cd tolerance (Derakhshani et al, 2020). Markertrait association study was conducted for As related traits using 704 SNPs.…”
Section: Quantitative Trait Locus Mappingmentioning
confidence: 99%
“…This strategy of combining results to screen candidate genes associated with various target traits is widely applied in many crops, such as cold stress response in rice seedling , cadmium tolerance in barley (Derakhshani et al 2020), fiber quality traits in cotton (Liu et al 2016), flowering time genes in oilseed rape (Jian et al 2019), and salt tolerance in rice (Wang et al 2017). By adopting the same approach, a few studies have also been conducted in soybeans to predict candidate genes for traits like pod dehiscence (Hu et al 2019) and low-phosphorus stress (Zhang et al 2017a).…”
Section: Introductionmentioning
confidence: 99%